Does an educational intervention improve parents’ knowledge about immunization? Experience from Malaysia - Awadh, Ammar Ihsan JawaD; Hassali, Mohamed Azmi; Al-lela, Omer Qutaiba; Bux, Siti Halimah; Elkalmi, Ramadan Mohamed Mahmod; Ab. Hadi, Hazrina (BioMed Central Ltd, 2014)
Background: Parents’ knowledge about immunization is an important predictor factor for their children’s immunization status. The aims of this study were to assess parents’ knowledge and to evaluate the effect of a short educational intervention on improving parents’ knowledge of childhood immunization.